Digital Consumerism and Islamic Ethics: Investigating E-Commerce Influence among Santri Students - Ahmad Thoriq Khairullah (Multidisciplinary Journal of Contemporary Islamic Discourse, 2026)
Consumption is the activity of using or reducing the utility of goods or services to fulfill human needs, either gradually or immediately. In the digital era, e-commerce has become a significant platform for buying and selling transactions using electronic media. One common form of e-commerce is the marketplace. This study aims to explain whether e-commerce influences consumption behavior based on the principles of Islamic economics among students of Ma’had Ulil Albab Lil Banin. The novelty of this research lies in its focus on Islamic boarding school students who are increasingly engaging with online shopping, potentially shifting their consumption patterns and ethical considerations. This study is motivated by the growing use of digital platforms among students, which raises questions about the alignment of their consumption behavior with Islamic values. A quantitative research method was used by collecting primary data through structured questionnaires. The results show that e-commerce does have an influence on consumption behavior, particularly in aspects such as frequency of purchases, types of goods selected, and purchasing motivations. However, the understanding and application of Islamic economic ethics in digital transactions vary among the respondents. The findings imply that there is a need to enhance awareness and education on ethical consumption within the context of Islamic economics, especially for young consumers in religious educational environments. This research contributes to the ongoing discussion on how faith-based values can guide modern consumer behavior in a digital society.